Penerapan Metode Case Based Reasoning Untuk Diagnosa Penyakit Kulit Akibat Virus Eksantema Berbasis Web - Parwan Harahap; Jeperson Hutahaean; Muthia Dewi (Building of Informatics, Technology and Science (BITS), 2022)
In the current condition of the patient, if he has experienced early symptoms of skin disease due to the exanthema virus, it is felt that he cannot directly consult with a dermatologist because of the high cost and limited time for specialists to carry out activities in the hospital. So the author needs to make an expert system application that can overcome this. Through this application, users can consult with the system like consulting an expert to diagnose symptoms that occur to users and find solutions to problems encountered. This expert system is made by providing appropriate or not or with several choices of answers that are recommended from the symptoms that occur. System. Diagnosing skin diseases due to exanthema virus, the author uses the Case Based Reasoning method. The CBR method is a weighting technique by comparing new cases with old cases. With the diagnosis based on the data provided by the patients and experts then analyzed by case based reasoning method and stored as a knowledge database in the expert system. So that this expert system can help to take solutions for handling problems when patients suffer from skin diseases due to the Exanthema Virus.